Biomorphological peculiarities and demographic structure of populations Pulsatilla bohemica (Skalický) Tzvelev under conditions of different belonging floristic complexes and antropogenic pressing (CHORNOMORSKI BOTANICAL JOURNAL, 2014)
Pulsatilla bohemica (Skalický) Tzvelev – rare species included in the Red Book of Ukraine half efemeroid, monocentric kaudeks of polycarpic. The article describes the features of spatial and demographic structure of the populations of P. bohemica in the reserves (national park "Bug Guard") and urbanized (suburban zone of Kiev metropolis) territories. Complex flora of affinity, breadth of ecological and coenotic activity, especially population structure of the species in their optimum and the northern limits of the range are analysed. The major anthropogenic factors that had a negative impact on populations of P. bohemica were studied. Proposed conservation actions ex situ and in situ.
Keywords: rare species, demographic structure of populations, urbanization, phytosozology.